(untitled) (Politeja, 2025)
INFORMATION ENVIRONMENT AND RUSSIAN AND CHINESE INFLUENCE OPERATIONS IN IRAQ The article presents an analysis of the information environment in Iraq and the Russian and Chinese FIMI (Foreign Information Manipulation and Interference) operations conducted there, targeting Western influence, propagating the Russian narrative and building their own resources of influence. For this purpose, the social and psychological sensitivities of the local societies are exploited in order to appropriately adjust the narratives. The research presented in this article is related to the Shaffaf project, carried out by the Info Ops Polska Foundation in order to counter influence and disinformation operations conducted in the Middle East, which target the image of Poland and the West as well as democratic values. The methodological basis is the NATO doctrine „Allied Joint Doctrine for Information Operations”.